The complete guide to the GATE: mechanical engineering - Trishna Knowledge Systems (Pearson, 2013)
The complete guide to the GATE: mechanical engineering / Trishna Knowledge Systems. -- New Delhi: Pearson, 2013 153.94621 T837 No. of Copies : 1